The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/htj.21793
|View full text |Cite
|
Sign up to set email alerts
|

Year around distilled water production, energy, and economic analysis of solar stills—A comparative study

Abstract: In this paper, a year around energy efficiency (EnE) and economic analysis of single slope solar still (SSSS), the single slope solar still with glass cooling (SSSSGC), the single slope solar still with basin heating (SSSSBH), and the single slope solar still with glass cooling and basin heating (SSSSGCBH) was carried out based on the distilled water production. The annual yield production from the SSSS, SSSSGC, SSSSBH, and SSSSGCBH were 476.16, 637.44, 970.24, and 1167.36 kg, respectively. The yearly yield pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The most prominent passive techniques can be mentioned such as using energy absorbing/storing materials (sands, cement, and marble pieces) [ [42] , [43] , [44] ], porous media [ 45 , 46 ], utilizing phase change materials (PCMs) [ [47] , [48] , [49] , [50] ], using wicks [ [51] , [52] , [53] ], fins [ 54 , 55 ], internal/external reflectors [ [56] , [57] , [58] ], film cooling [ [59] , [60] , [61] ], increase the rate of heat and mass transfer by utilizing different nanoparticles in absorber/fluid/cover of solar stills [ [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] ]. Meanwhile, integration with humidification-dehumidification systems [ 71 , 72 ], thermoelectric modules (for heating and cooling) [ 73 , 74 ], and external/internal condensers [ 75 , 76 ] are another modifications for enhancing the performance of system. Furthermore, utilizing various solar collectors such as flat plate collector (FPC) [ [77] , [78] , [79] , [80] ], solar dish concentrator (SDC) [ 81 , 82 ], parabolic trough concentrator(PTC) [ 83 , 84 ], Fresnel lens (FL) [ 85 , 86 ], evacuated tube collector (ETC) [ [87] , [88] , [89] , [90] ], mini/shallow solar pond [ 91 , 92 ], and photovoltaic (PV) and photovoltaic/thermal (PV/T) [ [93] , ...…”
Section: Solar Stillmentioning
confidence: 99%
“…The most prominent passive techniques can be mentioned such as using energy absorbing/storing materials (sands, cement, and marble pieces) [ [42] , [43] , [44] ], porous media [ 45 , 46 ], utilizing phase change materials (PCMs) [ [47] , [48] , [49] , [50] ], using wicks [ [51] , [52] , [53] ], fins [ 54 , 55 ], internal/external reflectors [ [56] , [57] , [58] ], film cooling [ [59] , [60] , [61] ], increase the rate of heat and mass transfer by utilizing different nanoparticles in absorber/fluid/cover of solar stills [ [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] ]. Meanwhile, integration with humidification-dehumidification systems [ 71 , 72 ], thermoelectric modules (for heating and cooling) [ 73 , 74 ], and external/internal condensers [ 75 , 76 ] are another modifications for enhancing the performance of system. Furthermore, utilizing various solar collectors such as flat plate collector (FPC) [ [77] , [78] , [79] , [80] ], solar dish concentrator (SDC) [ 81 , 82 ], parabolic trough concentrator(PTC) [ 83 , 84 ], Fresnel lens (FL) [ 85 , 86 ], evacuated tube collector (ETC) [ [87] , [88] , [89] , [90] ], mini/shallow solar pond [ 91 , 92 ], and photovoltaic (PV) and photovoltaic/thermal (PV/T) [ [93] , ...…”
Section: Solar Stillmentioning
confidence: 99%
“…In their study, Parsa et al [ 210 ] found that the combination of thermoelectric cooling and water film cooling could contribute to approximately 26% of the total water production. Meanwhile, Manokar et al [ 211 ] were able to increase freshwater production by 60% by employing thermoelectric cooling on the glass covering. Additionally, Khanmohammadi et al [ 212 ] achieved a 30% increase in average freshwater production through continuous cooling of a double‐glazed glass covering using a thermoelectric module.…”
Section: Enhancing Desalination Via Condensationmentioning
confidence: 99%
“…Previous studies proved that solar stills are capable to separate a wide range of organic and inorganic impurities from pharmaceutical and chemical compounds to biological contaminations. Various approaches also applied to increase the efficiency of solar stills including using different solar collectors [19] , [20] , [21] , reflectors [15] , wick materials [22] , low-cost energy storage [23] , heat localized materials [24] thermoelectric [ 25 , 26 ], phase change materials (PCM) [27] , [28] , [29] , and nanoparticles [30] , [31] , [32] , [33] . Interestingly, nanoparticles in solar stills have been attracted huge attentions of researchers due to their antibacterial characteristics against pathogens [34] , [35] , [36] .…”
Section: Solar Water Treatmentmentioning
confidence: 99%